2014
DOI: 10.1016/j.febslet.2014.04.049
|View full text |Cite
|
Sign up to set email alerts
|

Chaperonin‐containing TCP‐1 complex directly binds to the cytoplasmic domain of the LOX‐1 receptor

Abstract: Lectin-like oxidized low-density lipoprotein receptor (LOX-1) is a scavenger receptor that binds oxidized low-density lipoprotein (OxLDL) and has a role in atherosclerosis development. The N-terminus intracellular region (cytoplasmic domain) of LOX-1 mediates receptor internalization and trafficking, potentially through intracellular protein interactions. Using affinity isolation, we identified 6 of the 8 components of the chaperonin-containing TCP-1 (CCT) complex bound to LOX-1 cytoplasmic domain, which we ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…CCT was previously shown to bind to the cytoplasmic domain of the LOX-1 [Lectin-like oxidized low-density lipoprotein (LDL) receptor-1]receptor and regulates its trafficking ( 28 ). Alignment of the LOX-1 receptor cytoplasmic domain sequence (residues 1 to 33) with Orai1 shows significant homology within the Orai1-ICL (residues 144 to 173) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…CCT was previously shown to bind to the cytoplasmic domain of the LOX-1 [Lectin-like oxidized low-density lipoprotein (LDL) receptor-1]receptor and regulates its trafficking ( 28 ). Alignment of the LOX-1 receptor cytoplasmic domain sequence (residues 1 to 33) with Orai1 shows significant homology within the Orai1-ICL (residues 144 to 173) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The role of CCT in protein trafficking, in addition to its well-defined function as a folding chaperonin, is not limited to Orai1. In addition to its role in regulation trafficking of the Lox-1 receptor ( 28 ), a growing body of evidence suggests that CCT, through its association with the Bardet-Biedl syndrome (BBS) complex, plays a role in protein trafficking at the base of cilia ( 41 43 ). BBS is an autosomal recessive genetic disease in humans belonging to the ciliopathy spectrum disorders ( 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…The gene, JOSD1 , has been reported to be upregulated in peripheral blood mononuclear cells in those with asymptomatic myocardial dysfunction. [ 49 ] CCT6P1 is the pseudogene of the Chaperonin Containing TCP1 (CCT) Subunit 6 gene. The protein of this gene is one of the subunits of the CCT complex.…”
Section: Discussionmentioning
confidence: 99%
“…We recently demonstrated that LOX-1 binds directly to TRiC in endothelial cells and that treatment of cells with OxLDL causes disassociation of the LOX-1/TRiC complex [ 120 ]. TRiC also is required for the assembly and function of a complex that includes silencing mediator for retinoid or thyroid hormone (SMRT) and histone deacetylase (HDAC) [ 121 ].…”
Section: Tric Binds To and Modulates Cancer Related Proteinsmentioning
confidence: 99%